Mothers' perceptions of care practices for children who underwent heart transplantation - Sarah Maria de Sousa Feitoza; Cristiana Brasil de Almeida Rebouças; Máguida Gomes da Silva; Silvania Braga Ribeiro (SciELO, 2016)
Abstract OBJECTIVE To learn mothers' perceptions of the main care practices that are to be administered after their children's heart transplantation, as well as the main difficulties they experience. METHOD A descriptive qualitative study conducted in March and April 2014, using the focus group technique for data gathering. Participants were 12 mothers who were monitoring their children in a hospital that is a reference for treating cardiopulmonary diseases. Speeches were recorded, transcribed, and organized around the care practices that the mothers performed after the children's heart transplantations, the mothers' main difficulties, their perceptions of their children's quality of life, and the use of educational materials to disseminate post-transplantation care practices. For data analysis, we used the content analysis technique. RESULTS The following were clarified: the schedule of immunosuppressive medication; food, environmental, and bodily and oral hygiene; the use of surgical masks; and keeping the children away from crowds. CONCLUSION The study contributed to the situational diagnosis of the care administered by the mothers of transplanted children.